IMPLEMENTASI TEACHING FACTORY UNTUK MENINGKATKAN MUTU LULUSAN SEKOLAH MENENGAH KEJURUAN NU MAARIF KUDUS - Esthi Kusumastuti; Muhdi; Rasiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of Vocational High School is to produce graduates who are competent and ready to enter DUDIKA and create their own jobs. So Vocational High Schools are required to be able to equip their graduates with competencies that are in accordance with the competencies needed at DUDIKA. Based on the Central Statistics Agency, the unemployment rate for the population of vocational school graduates is still very high, in February 2024 there were 1,621,672 vocational high school graduates who haven't worked yet (Central Statistics Agency, 1 August 2024). Thus, there needs to be a link and match between schools and DUDIKA, one of the programs is the implementation of a teaching factory. In implementing the teaching factory, it is necessary to study the success of its implementation using Edward III's theory, including communication, resources, disposition or characteristics and bureaucratic structure. The aim of this research is to describe the indicators of success of a teaching factory including Communication, Resources, Disposition and Bureaucratic Structure. This research method is qualitative research, data collection techniques are carried out by triangulation (combination) including interviews, observation and docuImentation. The data analysis technique uses qualitative descriptive analysis including data collection, data reduction, data presentation, verification and confirmation of conclusions. The results of the research show that the implementation of the teaching factory at SMK NU Maarif Kudus according to Edward III's theory is, 1) Communication ran very well, communication techniques carried out with socialization and coordination. 2) The resources that support the teaching factory were very adequate, 3) Disposition, all personnel have a strong commitment to implement the teaching factory and support from the school principal, 4) Bureaucratic structure. There was an organizational structure formed with implementing positions along with the main duties and functions of each position as well as standard operating procedures (SOP) as a reference for implementing the teaching factory.